PENJAWAB PESAN SMS OTOMATIS MENGGUNAKAN RASPBERRY PI DENGAN MENGGUNAKAN METODE BRUTE FORCE - Affandi, Luqman; Wahyuningsih, Dian (DINAMIKA DOTCOM, 2017)
SMS gateway technology still a reliable technology to send messages from the server to the user. SMS gateway consist of a computer as a server and modem as a sender or receiver of SMS messages, which work for 24 hours to serve the users. With the advance of small computer technology such as Raspberry Pi, the need to set up SMS gateway can be suppressed to replace the server. To break the SMS information from the user, requires a method. One of the method is brute force. The purpose of this research is to establish the message answering device / automatic SMS gateway using Rapberry Pi, which read the messages using brute force method. Steps that can be taken is to prepare Raspberry Pi with Operating System, Raspberry Pi installation andconnectivity with modem, SMS gateway program installation and sms auto reply application development. The research results prove that Rapberry Pi can be used as a substitute for SMS gateway server..Keywords: raspberry pi, sms gateway, brute force